2013
DOI: 10.4136/ambi-agua.1187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of coagulation/flocculation process in the landfill leachate treatment at the Municipal Wastewater Treatment Plant

Abstract: The combined treatment of leachate from urban solid waste landfills in a Municipal Wastewater Treatment Plant (MWTP) minimizes the implementation and operation costs of a landfill. This work investigated the combined treatment of the leachate from Morro do Céu Landfill in Niterói, RJ and sewage samples from Icaraí MWTP with different proportions (0, 0.5, 2.0 and 5.0 %). This MWTP features a physical chemical treatment followed by expulsion through a submarine emissary, and so the physical chemical treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
0
4
0
1
Order By: Relevance
“…Although not a monitored parameter for POTWs discharging limits, TOC is an important parameter to indicate the organic carbon concentration, as organic carbon or the compounds containing organic carbon are the major contributor to UV absorbance. Based on several previous published works, it was found that the amount of coagulant dose required for coagulation-flocculation process is directly related to the initial concentration of organic matter in the leachate sample (Assou et al, 2016;Campos et al, 2013;Malathi et al, 2016;Mojiri et al, 2013;Rui and Daud, 2011). Compared to these previous studies, in this study coagulant dose was applied in increment of 200 mg/L until a flat curve was obtained for organic matter removal to evaluate the coagulant dose required for coagulation-flocculation for two leachate samples that have significantly different water quality characteristics (especially organic matter and pH).…”
Section: Organic Matter Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not a monitored parameter for POTWs discharging limits, TOC is an important parameter to indicate the organic carbon concentration, as organic carbon or the compounds containing organic carbon are the major contributor to UV absorbance. Based on several previous published works, it was found that the amount of coagulant dose required for coagulation-flocculation process is directly related to the initial concentration of organic matter in the leachate sample (Assou et al, 2016;Campos et al, 2013;Malathi et al, 2016;Mojiri et al, 2013;Rui and Daud, 2011). Compared to these previous studies, in this study coagulant dose was applied in increment of 200 mg/L until a flat curve was obtained for organic matter removal to evaluate the coagulant dose required for coagulation-flocculation for two leachate samples that have significantly different water quality characteristics (especially organic matter and pH).…”
Section: Organic Matter Removalmentioning
confidence: 99%
“…show that the optimum pH required is 7 -10.5 for both ferric chloride and aluminum sulphate (Campos et al, 2013;Farrokhi et al, 2015;Malathi et al, 2016;Rui and Daud, 2011;Wang et al, 2009). In some practices, pH is adjusted before coagulation to improve the removal efficiency of primary treatment.…”
Section: /39mentioning
confidence: 99%
“…Leachate has been treated using biological processes, such as stabilization ponds or activated sludge; and using membranes, or other processes, such as adsorption, coagulation, and flocculation. However, due to the variable nature of the leachate, there is no consensus regarding which treatment is best (Campos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because the characteristics of the leachate are notably variable, there is not a clear consensus regarding the best treatment system. [13] The Powdered Activated Carbon Treatment (PACT) process was developed by DuPont in the 1970s. [14] The process is a sludge aerobic treatment using powdered activated carbon.…”
Section: Introductionmentioning
confidence: 99%